Delays in territorial development – case study of the Hungarian Sand Ridge Region - Kovács, András Donát. Autor; Farkas, Jenő Zsolt. Autor; Varjú, Viktor. Autor; Szalai, Ádám. Autor; Lennert, József. Autor; Hoyk, Edit. Autor; Csáki, Béla. Autor (IGiPZ PAN, 2023)
There are regions in Europe that are particularly vulnerable both environmentally and socially. Hungary’s Sand Ridge in the Danube Tisza Interfluve (Homokhátság in Hungarian) is considered such a region. The water balance of these lowland landscapes has been negative for decades, and complex ecological and social problems have escalated in parallel with aridification. Therefore, this region deserves special attention from the territorial development perspective. Over the last two decades, our successive studies have revealed that development policies in the region have been unsuccessful on multiple occasions, unable to alter the core negative trends significantly. We also noticed the mistakes and inertness of spatial planning when we worked on our current applied research: the Sand Ridge Regional Development Concept and Program. This study aims to explore deficiencies and shortcomings of the spatial policy and identify the factors that have slowed territorial development. Insights from interviews with experts and surveys conducted with local municipalities highlight that access to European Union funds has not alleviated long-standing conflicts. Resource-driven and uniform planning has become one of the main hindering factors. According to the experts, the necessary complex programs have not been implemented, and many initiatives have stalled. They also expressed concerns that Sand Ridge’s natural and social endangerment will continue to increase.
29 cm
Każdy numer posiada własny tytuł.
Keywords: Homokhátság; Węgry; planowanie regionalne; Sand Ridge; polityka przestrzenna; rozwój terytorialny; Homokhátság; Hungary; regional planning; Sand Ridge; spatial policy; territorial development